Copy number polymorphism in Fcgr3 predisposes to glomerulonephritis in rats and humans. - Aitman, T; Dong, R; Vyse, T; Norsworthy, P; Johnson, MD; Smith, J; Mangion, J; Roberton-Lowe, C; Marshall, A; Petretto, E; Hodges, MD; Bhangal, G; et al. (2006)
Identification of the genes underlying complex phenotypes and the definition of the evolutionary forces that have shaped eukaryotic genomes are among the current challenges in molecular genetics. Variation in gene copy number is increasingly recognized as a source of inter-individual differences in genome sequence and has been proposed as a driving force for genome evolution and phenotypic variation. Here we show that copy number variation of the orthologous rat and human Fcgr3 genes is a determinant of susceptibility to immunologically mediated glomerulonephritis. Positional cloning identified loss of the newly described, rat-specific Fcgr3 paralogue, Fcgr3-related sequence (Fcgr3-rs), as a determinant of macrophage overactivity and glomerulonephritis in Wistar Kyoto rats. In humans, low copy number of FCGR3B, an orthologue of rat Fcgr3, was associated with glomerulonephritis in the autoimmune disease systemic lupus erythematosus. The finding that gene copy number polymorphism predisposes to immunologically mediated renal disease in two mammalian species provides direct evidence for the importance of genome plasticity in the evolution of genetically complex phenotypes, including susceptibility to common human disease.